Students awareness on environmental quality in term of daily life routine / Noorlida Daud, Wan Noor AniraHj Wan Ali @ Yaacob & Anwar Fikri Abdullah - Noorlida, Daud; Wan Noor Anira, Wan Ali @ Yaacob; Anwar Fikri, Abdullah (2015)
Environmental quality can be defined as a set of properties and characteristics of the environment. Students should be concern about their routine on this environmental quality but unfortunately students nowadays lack of awareness towards the environmental quality. In fact some of them do not know that they have to take care of their hostel rooms, classrooms or studios. Therefore, the purpose of this study is to measure the level of understanding on the needs to maintain the rooms that they use. This study is also aimed to determine the level of environmental quality awareness among UiTM Perak’s students in Seri Iskandar. Questionnaire will be given to respondent, which is consisting of 50 students from Art and Design Faculty and 50 students from Architecture, Planning and Surveying Faculty.